Horrid Henry's hilariously horrid joke book - "Simon, Francesca" (Orion children's book Great Breatin, 2014)
Laugh your way through every day of the year with Horrid Henry as he presents 365 hilarious jokes for every possible occasion ... But is the last laugh on Henry?
Keywords: Wit and humor